Signature of quantum Griffiths singularity state in a layered quasi-one-dimensional superconductor - Enze Zhang (Nature Portfolio, 2018)
Whether the quantum Griffiths singularity state exists in one-dimensional (1D) systems remains elusive. Here, Zhang et al. report violation of the Pauli limit in the superconducting critical field and multiple phase transitions in the current-voltage hysteresis loops in a Ta2PdS5 nanowire, suggesting signatures of quasi-1D quantum Griffith singularity.